2015 American Academy of Clinical Neuropsychology (AACN) student affairs committee survey of neuropsychology trainees. Issue 5 (3rd July 2016) - Whiteside, Douglas M.; Guidotti Breting, Leslie M.; Butts, Alissa M.; Hahn-Ketter, Amanda E.; Osborn, Katie; Towns, Stephanie J.; Barisa, Mark; Santos, Octavio A.; Smith, Daniel
Abstract: Objective : Surveys of practicing neuropsychologists have been conducted for years; however, there have been no comprehensive surveys of neuropsychology trainees, which may result in important issues being overlooked by the profession. This survey assessed trainees' experiences in areas such as student debt, professional development, and training satisfaction. Method : Survey items were written by a task force of the AACN Student Affairs Committee (SAC), and neuropsychology trainees were recruited via neuropsychology-focused listservs. In total, 344 trainees completed the survey (75% female) and included participants from every region of the US and Canada. Results : Based on the survey questions, nearly half of all trainees (47%) indicated financial factors were the greatest limitation in their training. Student debt had a bimodal distribution; 32.7% had minimal debt, but 45% had debt >100, 000. In contrast, expected starting salaries were modest, but consistent with findings (80–100, 000). While almost all trainees intended to pursue board certification (97% through ABPP), many were 'not at all' or only 'somewhat' familiar with the process. Conclusions : Results indicated additional critical concerns beyond those related to debt and lack of familiarity with board certification procedures. The results will inform SAC conference programming and the profession on the current 'state of the trainees' in neuropsychology.